IL-6-induced long noncoding RNA MIR3142HG promotes tumorigenesis by interacting with thioredoxin-1 and STAT3 in human colorectal cancer - Daoquan Fang; Qian Feng; Baojian Zhou; Yangyang Liu; Yichu Lian; Yihui Zhang; Dichen Yang; Xintong Liu; Xiaomeng Shi; Wuhua Ni; Lei Jiang (Cellular & Molecular Biology Letters)
Abstract Background Colorectal cancer (CRC) is a prevalent and highly malignant neoplasm on a global scale, ranking as the second most widespread cause of cancer-associated death. Long noncoding RNAs (lncRNAs) control tumorigenic processes in CRC by modulating inflammatory signals. However, the precise mechanisms remain unknown. Methods LncRNAs regulated by thioredoxin-1 (Trx-1) and interleukin (IL)-6 were identified by RNA sequencing (RNA-seq). The effect of MIR3142HG on CRC growth, migration, and invasion was assessed through methods of cell counting kit-8 (CCK-8), colony formation assay, Transwell assay, and animal experimentation, respectively. The regulation of signal transducer and activator of transcription 3 (STAT3) on the MIR3142HG promoter was verified using chromatin immunoprecipitation (ChIP) and dual-luciferase reporter assays. The interaction of MIR3142HG with Trx-1 and STAT3 proteins was validated with RNA-binding protein immunoprecipitation (RIP) and RNA-pulldown experiments. Bioinformatics analysis and tissue microarray were utilized for evaluating the clinical value of MIR3142HG in CRC. Results We identified a lncRNA, MIR3142HG, regulated by Trx-1 knockdown and IL-6 treatment. Overexpression of MIR3142HG enhanced CRC cell proliferation, migration, and invasion, while its knockdown impaired these processes. STAT3 bound to the MIR3142HG promoter and activated its transcription. Upregulated MIR3142HG acted as a scaffold for the Trx-1/STAT3 complex to inhibit the degradation of Trx-1 and phosphorylated STAT3 (p-STAT3). In situ hybridization (ISH) results of CRC tissues indicated that MIR3142HG expression was significantly elevated during the early stages of CRC. Moreover, consistent with the Cancer Genome Atlas (TCGA) dataset, high MIR3142HG expression predicted better survival. Conclusions Our study identified a novel lncRNA MIR3142HG, which interacts with STAT3 and Trx-1 to promote CRC progression, providing a possible diagnostic target for CRC. Graphical Abstract